Photocatalytic degradation of methyl orange using TiO2:Mg2+/zeolite composite under visible light irradiation - Afsaneh Mozayyeni; Jafar Mahmoudi (Journal of Particle Science and Technology, 2020)
Photodegradation of methyl orange was investigated using synthesized TiO2:Mg2+/zeolite as the photocatalyst. The photocatalyst was characterized by X-ray, XRF, FT-IR, and SEM. The photocatalytic activities of TiO2:Mg2+/zeolite samples were evaluated in the degradation of methyl orange under visible light irradiation. The appropriate content of Mg in the composite was obtained as 4.711 wt% with 100% removal of methyl orange in 50 minutes. The influence of irradiation time, catalyst concentration, pH, and calcination temperature on the photodegradation of methyl orange was investigated, and the appropriate amounts obtained for these parameters were 60 min, 5 g/l, 10, and 450 °C, respectively. The degradation of methyl orange over TiO2:Mg2+/zeolite was about 82% after five cycles, confirming the suitable reusability of the photocatalyst.